The Maqashid Sharia Index: An Innovative Tool for Evaluating Corporate Performance in IDX-MES BUMN 17 - Fitria, Ana; Desiana, Rina; Azzuhra, Alfia; Iskandar, Evy; Marwa, Inayah Putri (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2024)
Company performance is not only focused on internal profits but also considers external benefits, which can be evaluated using the Maqasid Sharia Index (MSI) method. This research focuses on companies listed on the IDX-MES BUMN 17 Sharia Index, launched on April 29, 2021. The study incorporates three key concepts: individual education (tahzib al-fard), the establishment of justice (iqamat al-adl), and the promotion of welfare (jalb al-mashlahah). A descriptive quantitative analysis was conducted by measuring performance through weighting and ranking based on performance indicators derived from the annual reports of 14 companies for the period 2021-2023. The TLKM achieved the highest MSI score with a ratio of 32.13%, while PTPP ranked last with a ratio of 17.38%. Overall, the companies listed on the IDX-MES BUMN 17 index demonstrated low performance based on the MSI, with ratios ranging from 17% to 30%, and an average ratio of 21.52% out of a total weight of 100%